Utilizacion de los subproductos del cafe en la reproduccion del hongo entomopatogeno beauveria baáiana - Carr, A.=700 1 Bell, N.; Toledo, C.; Perez, I.
(Es, En)
Ilus., 12 ref.
Keywords: COFFEA ARABICA; BEAUVERIA BAáIANA; HONGOS ENTOMOPATOGENOS; CUBA; CAFE PERGAMINO